2015
DOI: 10.1021/acsami.5b03509
|View full text |Cite
|
Sign up to set email alerts
|

Selective Formic Acid Production via CO2 Reduction with Visible Light Using a Hybrid of a Perovskite Tantalum Oxynitride and a Binuclear Ruthenium(II) Complex

Abstract: A hybrid material consisting of CaTaO2N (a perovskite oxynitride semiconductor having a band gap of 2.5 eV) and a binuclear Ru(II) complex photocatalytically produced HCOOH via CO2 reduction with high selectivity (>99%) under visible light (λ>400 nm). Results of photocatalytic reactions, spectroscopic measurements, and electron microscopy observations indicated that the reaction was driven according to a two-step photoexcitation of CaTaO2N and the Ru photosensitizer unit, where Ag nanoparticles loaded on CaTaO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
121
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 130 publications
(127 citation statements)
references
References 26 publications
5
121
1
Order By: Relevance
“…For the development of artificial photosynthetic schemes, variousm etal complexes [1][2][3][4][5][6][7][8][9][10][11][12][13] and semiconductors, [14][15][16][17][18][19] as well as their hybrids, [20][21][22][23][24][25][26][27][28] have been examined as photocatalystsf or CO 2 reduction. For the development of artificial photosynthetic schemes, variousm etal complexes [1][2][3][4][5][6][7][8][9][10][11][12][13] and semiconductors, [14][15][16][17][18][19] as well as their hybrids, [20][21][22]…”
Section: Introductionmentioning
confidence: 99%
“…For the development of artificial photosynthetic schemes, variousm etal complexes [1][2][3][4][5][6][7][8][9][10][11][12][13] and semiconductors, [14][15][16][17][18][19] as well as their hybrids, [20][21][22][23][24][25][26][27][28] have been examined as photocatalystsf or CO 2 reduction. For the development of artificial photosynthetic schemes, variousm etal complexes [1][2][3][4][5][6][7][8][9][10][11][12][13] and semiconductors, [14][15][16][17][18][19] as well as their hybrids, [20][21][22]…”
Section: Introductionmentioning
confidence: 99%
“…[22] Thus,weinitially performed CO 2 reduction under 13 CO 2 atmosphere,a nd collected No-D 1 H-NMR spectra to verify the carbon source of formate.U nfortunately,t he low activity/sensitivity of No-D NMR method did not allow the detection of any signal of products from RuRu' '/Li 2 LaTa 2 O 6 N. Accordingly,n anoparticulate Ag (1.5 wt %) was in prior deposited on Li 2 LaTa 2 O 6 Nt op romote CO 2 reduction, as reported previously. [10,11] Deposition of metallic Ag nanoparticles with 20-30 nm in size on Li 2 LaTa 2 O 6 Nw as confirmed by means of XAFS and TEM observations (Supporting Information, Figures S11 and S12). This modification improved the formate production rate (entry 5, Table 1).…”
Section: +mentioning
confidence: 68%
“…We previously reported that prior modification of CaTaO 2 Nw ith Ag nanoparticles improved the formate production in the visible-light Z-scheme CO 2 reduction with RuRu' '. [10] However,e ven without modification of Ag, the activity of RuRu' '/ Li 2 LaTa 2 O 6 Nw as two-fold higher than that of the optimized RuRu' '/Ag/CaTaO 2 N( entry 8). These results clearly indicate great potentials of layered oxynitride materials as ap hotocatalyst.…”
Section: +mentioning
confidence: 97%
See 2 more Smart Citations